Synthesis of Applied Behavior Analytic Interventions for Packing in Pediatric Feeding Disorders. Issue 2 (March 2018) - Silbaugh, Bryant C.; Swinnea, Samantha; Penrod, Becky
Packing, which consists of holding food in the mouth for an extended time during meals, is a form of disordered feeding associated with pediatric feeding disorders. The behavior can disrupt the pace and completion of a meal and lead to increased risk of choking, inadequate food and liquid intake, and elevated caregiver stress associated with mealtimes. Applied behavior analysis research has developed and evaluated behavioral interventions to improve feeding by reducing packing. This systematic review extends prior research by synthesizing characteristics of the packing intervention literature, evaluating the certainty of the evidence provided by studies, identifying potential directions for future research, and discussing the results in the context of evidence-based practice.